“Uso de Flashcards como estrategia didáctica para la comprensión lectora de cognados falsos del inglés como lengua extranjera” - Ruiz Fachin de Otoya, Jacqueline Susan (2019)
ABSTRACT In the present work we have investigated the use of flashcards as a didactic strategy to identify false cognates in English texts, understand their meaning taking into account the context and then understand the texts in English. Flashcards are tools that will help third-year high school students differentiate between a true cognate and a false cognate. For the realization of this thesis the experimental method was taken into account to contrast the effectiveness of the flashcards in the reading of texts in English. The students were selected randomly. The initial test (pre-test) was applied to both groups (control and experimental), as well as learning sessions with simple readings and contextualized to the reality of the students. The learning sessions for the experimental group were structured following the sequence of pre, during and post reading comprehension. This research work compared the results of the results of the post-tests and the dimensions as details or specific information, vocabulary and sequence of events in both groups and found a significant difference (p < 0.05) that supports the thesis of the positive influence of the flashcards in the understanding of false cognates in English readings.